Surge of Cyber Scams during the COVID19 Pandemic: Analyzing the Shift in Tactics - Kacheru, Goutham; Bajjuru, Rohit; Arthan, Nagaraju (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The global society was majorly impacted due to the COVID19 pandemic, introduction of new normal and providing different opportunities for the cyber criminals. The paper looks into the impact of the pandemic on cybercrime, pointing out how attacks have become more commonplace and varied during a time when people are more fearful. It shows how careful examination of cyber-attacks in light of significant events in the real world reveals new techniques being applied by them. At first, there was a certain lag between the start of the pandemic and cyber-attacks related to it. However, they gradually went up until we were receiving multiple unique attacks per day. Based on data from the UK, it shows (and uses published studies where applicable) how cybercriminals took advantage of within these situations during a series of major events or government announcements to identify and create relevantly targeted campaigns. Certain recommendations are made which may be able to mitigate cybersecurity impact and help guides individuals as they deal with the changing challenge landscape.